2012
DOI: 10.1002/ange.201200063
|View full text |Cite
|
Sign up to set email alerts
|

Jüngste Fortschritte in der Azaborin‐Chemie

Abstract: Die Chemie der Organoborverbindungen wurde im Wesentlichen durch ihre Verwendung als leistungsfähige Reagentien in der organischen Synthese beherrscht. Neuerdings hat sich die Einbindung von Bor als Bestandteil einer funktionellen Zielstruktur als ein geeigneter Weg erwiesen, um Diversität in organischen Verbindungen hervorzurufen. Eine üblicherweise angewendete Strategie ist der Austausch einer CC‐ gegen eine isoelektronische BN‐Einheit. Besonders die BN/CC‐Isosterie von Arenen erfuhr im vergangenen Jahrzehnt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(12 citation statements)
references
References 101 publications
0
10
0
2
Order By: Relevance
“…To estimate the effect of this on the aromatic stabilization of the C 5 Br ing in 1-boraphenalenes relative to isoelectronic carbocations the isomerization method was used (calculations at the B3LYP/6-311G(d,p) level, Eq. While it has been demonstrated numerous times that the LUMOs of Bd oped PA Hs and carbocation analogues are often similar in nature, [6] to fully understand the properties of these isoelectronic pairs consideration of the occupied p orbitals is also essential. [18] This revealed that this 1-boraphenalene has am uch lower aromatic stabilization energy than the isoelectronic carbocation congener.T he lower aromatic stabilization energy for the 1-boraphenalenes was supported by an isodesmic reaction (Eq.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the effect of this on the aromatic stabilization of the C 5 Br ing in 1-boraphenalenes relative to isoelectronic carbocations the isomerization method was used (calculations at the B3LYP/6-311G(d,p) level, Eq. While it has been demonstrated numerous times that the LUMOs of Bd oped PA Hs and carbocation analogues are often similar in nature, [6] to fully understand the properties of these isoelectronic pairs consideration of the occupied p orbitals is also essential. [18] This revealed that this 1-boraphenalene has am uch lower aromatic stabilization energy than the isoelectronic carbocation congener.T he lower aromatic stabilization energy for the 1-boraphenalenes was supported by an isodesmic reaction (Eq.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[6,13] In this area the combination of alkyne borylative cyclisation [14] and intramolecular boron-Friedel Crafts enabled the formation of boracycles (Scheme 1, top). [6,13] In this area the combination of alkyne borylative cyclisation [14] and intramolecular boron-Friedel Crafts enabled the formation of boracycles (Scheme 1, top).…”
mentioning
confidence: 99%
“…[7] Advances in the synthetic work on azaborinine derivatives up to 2012 have been reviewed by Liu and co-workers. [8] Until recently, only very few examples of 1,4-azaborinines have been reported, all of which possessed benzo-fused polycyclic structures. [9] Very recently, Braunschweig et al reported the first successful synthesis of a monocyclic 1,4-azaborinine derivative, namely, 1,4-ditert-butyl-1,4-azaborinine (Scheme 1), by using a rhodiumcatalyzed tandem [2+2]/[2+4] cycloaddition process.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Accordingly, variouso rganoboron p-conjugated molecules and polymers have been developed for organico ptoelectronic materials andd evices. [21][22][23][24][25] The boron-nitrogen coordination bond (B ! N) is one typical kind of Lewisa cid/base pair.…”
mentioning
confidence: 99%